O monstro no ecilpse ético: um estudo discursivo-midiológico da encarnação gótica de "Barbazul" - Messias, José Victor Rodrigues de Andrade (Universidade Federal de São Carlos, 2023)
Anabella López’s Barbazul (2017) is an editorial object (SALGADO, 2020) that evokes a discursive ethos (MAINGUENEAU, 2008), a self-image, that is ominous. Our hypothesis in this undergraduate paper is that this book also has in itself another editorial object, the monster Barbazul which, as we defend, can be read as a “neomonster”. A monster, as in Halberstam (1995), represents a threat arising from minority groups, marginalized ones, towards dominant groups, in other words, monsters are threats against the current social system: upper class, white, heterosexual, cisgender and read as masculine people. The neomonster is the opposite of that and, in this case, we know Barbazul as the representation of all that once was threatened by the monster figure. Barbazul (2017) is also a fairy tale, but it’s a gothic fairy tale, its materialities are inscribed by a language code (MAINGUENEAU, 2004:2020) that goes back to the narratives about the gothic people which, by the European society’s point of view, were a barbarian group responsible for the outset of the “Dark Age” by the fall of the Roman Empire. Thereby we start from the discursive-mediologic methodological perspective developed in the scope of the research group Comunica – Inscrições Linguísticas na Comunicação (UFSCAR/CEFET-MG, CNPq), part of the Laboratório de Escritas Profissionais e Processos de Edição (LABEPPE) network to analyze the output of senses by the mobilized elements in the material formalization (FLUSSER, 2007). This analysis runs through diachronic and synchronic aspects of the studied editorial objects, the book and the neomonster, so we can understand how a children’s literary genre, the fairy tale, becomes part of what we know as horror, in a process we explain as an ethical eclipse.
The monster on the ethic eclipse: a discursive-midiologic study on the gothic incarnation of "Barbazul"
Keywords: Ethos discursivo; Formalização material; Monstros; Midiologia; AD; Discursive ethos; Material formalization; Mediology; Monsters; LINGUISTICA, LETRAS E ARTES::LINGUISTICA